Motor competence and compliance with physical activity recommendations in Chilean schoolchildren - Martinez-Lopez, Nicolas; Estevan, Isaac; Candia-Cabrera, Paulina; Aguilar-Farias, Nicolas; Carcamo-Oyarzun, Jaime (Frontiers in Psychology, 2024)
The development of motor competence is thought to be a crucial precursor to raising the trajectory of PA throughout a person's life. The objectives of this study are to determine motor competence and the daily time of moderate and vigorous physical activity of students in 5th and 6th grade elementary in Chile, and to establish whether there are differences in motor competence according to sex and compliance with physical activity recommendations. 368 schoolchildren (M=11.10 years; 54.3% girls) participated. To assess motor competence, the MOBAK 5-6 test was used. Physical activity was measured using ActiGraph wGT3X-BT® accelerometers. Boys (M = 3.65, SD = 2.14) showed better performance than girls (M=2.39, SD=1.80) in Object Control (p≤0.001, PS=0.67). For Self-Movement, the girls (M=2.72 SD=2.14) performed better than the boys (M=2.40 SD=1.86); however, there were no significant differences between the two sexes (p=0.257). Boys (M=48.4 SD=22.8) presented more daily minutes of moderate and vigorous physical activity than girls (M=35.9 SD=16.9), with statistically significant differences (p≤0.001, PS=0.67). About MC according to compliance with the physical activity recommendations, only in Object Control there is a statistically significant difference (p≤0.001; PS=0.29) between the students who comply with the recommendations (M=4.28 SD=2.12) and those who do not achieve the recommended minutes (M=2.67 SD=1.29). By contrast, an analysis of Self-Movement found no significant difference (complies: M=2.73 SD=1.97; does not comply: M=2.54 SD=2.04; p=0.408) between the two groups. It is necessary to generate instances that develop motor competence in all its dimensions to promote higher levels of moderate to vigorous physical activity.